3D model retrieval using MeshSIFT descriptor and fuzzy C-means clustering - Hamza, Najlaa Abd; Jafer, Shatha Habeeb; Hadi, Raghad Mohammed (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
A huge number of three-dimensional models exists on the internet, due to the fact that there are now more three-dimensional modelling and digitizing tools available for ever-increasing applications. The procedures for retrieval of three-dimensional models have thus become even more essential. The subject of this paper is a shape retrieval of 3D models that are signified as triangle meshes. We propose a new method which first computes the descriptor of 3D models through extracting its features, and then divides a model into clusters depending on a descriptor which is invariant to scale and orientation. A Fuzzy C-means clustering method is utilized for dividing the model into clusters. The superior performance and benefits of our method are shown in the results.